Optimization and evaluation of the physical stability of shampoo preparations containing virgin coconut oil and aloe vera extract - Oktosa, Megi; Nareswari, Tantri Liris; Syafitri, Erga; Adliani, Nur (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2024)
Background: Hair is crucial for both aesthetic appearance and protection against sun damage. Shampoo is vital in hair care, often formulated with natural ingredients to enhance its effectiveness. Virgin coconut oil (VCO) and aloe vera extract are two ingredients known for their roles as moisturizers and conditioners, as well as nutrients and emollients. Objective: The study aimed to evaluate and optimize the stability and physical characteristics of shampoo containing VCO and aloe vera. Methods: The primary surfactant, sodium lauryl sulfate (SLS), was tested in concentrations of 2%, 4%, 6%, 8%, and 10%. The shampoos were prepared using an emulsification method and were evaluated based on organoleptic properties, homogeneity, pH, specific gravity, and viscosity. The formula that met all Indonesia National Standard (SNI) requirements was selected for further testing, including a cycling test to assess stability. Results: The findings indicate that the formula 5 (F5) containing 10% sodium lauryl sulfate exhibited optimal physical characteristics. Throughout six rounds of cycling tests, no phase separation was observed in F5, underscoring its stability. Conclusion: The optimized shampoo formula containing VCO and aloe vera (F5) demonstrated compliance with the required physical characteristics and stability standards. This formula presents a viable option for effective hair care, combining the beneficial properties of its natural ingredients with chemical stability.